2018
DOI: 10.1080/09603123.2018.1543799
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with plasma concentrations of polychlorinated biphenyls (PCBs) and dichlorodiphenyldichloroethylene (p,p’-DDE) in the Canadian population

Abstract: This study describes blood plasma concentrations of PCBs and p,p'-DDE in the Canadian population aged 20-79 years. PCBs and p,p'-DDE were measured in 1668 participants in the Canadian Health Measures Survey, Cycle 1 (2007-2009). We investigated how concentrations vary by sociodemographic, anthropometric, and lifestyle variables, identified factors associated with exposures, and evaluated concentrations against healthbased guidance values. Congeners of PCB most commonly detected were PCB-138, PCB-153, and PCB-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…For five chemicals, indicated in Table 2 with an asterisk (*), the plasma concentrations of the adults were significantly (p < 0.002) different from those of the children. Adults had higher levels of most PCBs and organochlorine pesticides than children, a finding that is consistent with existing research showing that persistent organic pollutant concentrations increase with age (Alcock et al 2000;Nichols et al 2007;Singh et al 2019). Some chemicals, notably fluorene and PCBs 18 and 101, were higher in children than adults although the trend was not significant.…”
Section: Group Comparisonssupporting
confidence: 87%
“…For five chemicals, indicated in Table 2 with an asterisk (*), the plasma concentrations of the adults were significantly (p < 0.002) different from those of the children. Adults had higher levels of most PCBs and organochlorine pesticides than children, a finding that is consistent with existing research showing that persistent organic pollutant concentrations increase with age (Alcock et al 2000;Nichols et al 2007;Singh et al 2019). Some chemicals, notably fluorene and PCBs 18 and 101, were higher in children than adults although the trend was not significant.…”
Section: Group Comparisonssupporting
confidence: 87%
“…They can be categorized into dioxin-like and non-dioxin-like PCBs based on the number and the substitution sites of chlorine atoms on the biphenyl rings ( 1 ). Although PCBs have been banned since the last century owing to their environmental and human toxicity, they are still present at measurable levels in the environment and in human tissues and plasma ( 2 4 ). Their high lipophilicity and resistance to biodegradation enable PCBs to bioaccumulate and biomagnify throughout the food chain, making food consumption the primary route of human exposure to PCBs ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…These two congeners are predominant congeners found in food (7) and in human plasma (2). The plasma level of PCBs is 0.635 µg/L in the Canadian general population (4). The PCB exposure disrupts host metabolism (8,9) and increases the risk of metabolic disorders including obesity, type 2 diabetes and liver diseases (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Together, this cluster of CVD risk factors is considered metabolic syndrome, which has been positively associated with high plasma concentrations of p,p'-DDE [20]. Numerous epidemiological studies show that p,p'-DDE is found within human plasma and adipose tissue due to its high lipophilicity [21], however, it is unclear which lipids p,p'-DDE associates with to facilitate its activity [22,23]. These characteristics of high persistence allow p,p'-DDE to affect adipose tissue and lipid metabolism while it is stored within the body for an estimated halflife of 6.2-8.9 years [21,24].…”
Section: Introductionmentioning
confidence: 99%